One-Pot Regioselective Synthesis of 2,5,6,7-Tetrahydroimidazo [1,2-a]imidazol-3-ones Starting from (Vinylimino)phosphoranes - Tan, Fen; Meng, Zheng-Zheng; Xiong, Xiao-Qin; Zeng, Guo-Ping; Ding, Ming-Wu (Synlett, 2019)
A new, one-pot, regioselective preparation of 2,5,6,7-tetrahydroimidazo[1,2-a]imidazol-3-ones by a sequential aza-Wittig/nucleophilic addition/cyclization reaction was developed. The aza-Wittig reactions of ethyl (2Z)-3-aryl-2-[(triphenylphosphoranylidene)amino] acrylates with aryl isocyanates produced carbodiimide intermediates that were then treated sequentially with 2-aminoethanol and tosyl chloride/triethylamine to give the corresponding (2Z)-2-[(substituted)benzylidene]-2,5,6,7-tetrahydro-3H-imidazo[1,2-a]imidazol-3-ones in good overall yields and with high regioselectivity.
Keywords: imidazoimidazolone; aza-Wittig reaction; nucleophilic addition; regioselectivity